Reformed Hermeneutics: A hermeneutic that fits the occasion? - Fourie, Wynand (Stellenbosch Theological Journal, 2023)
Despite the Spirit-nature of Calvin’s hermeneutic, he does not provide the reader with either explanations or concrete examples of the way in which the Spirit is involved in the interpretation process (Nel 2020:8). In this article, I present a contribution to the ways in which the hermeneutical process of communal spiritual discernment during the council of Jerusalem, as recorded in Acts 15:1–35, can engage wit this aperture in Calvin’s hermeneutic. As an integral part of this communal spiritual discernment process, the engagement of the council, under the guidance of the Holy Spirit, with the biblical text is also highlighted. Reformed hermeneutics can, from the perspective of a process of communal spiritual discernment, be described as a hermeneutic that fits the occasion. [1] Keener (2016:33 of 44) indicates that a Pentecostal hermeneutic is simply a Christian hermeneutic. Ultimately, a Christian hermeneutic is a Spirit hermeneutic.